Informing emergency care for all patients: The Registry for Emergency Care (REC) Project protocol. (27th June 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Mitra, Biswadev; Noonan, Michael P; Hiller, Ryan; Brichko, Lisa; Luckhoff, Carl; Paton, Andrew; Smit, De Villiers; Cameron, Peter A
Abstract: Objective: In Australia, the current ED burden related to COVID‐19 is from 'suspected' rather than 'confirmed' cases. The initial aim of the Registry for Emergency Care (REC) Project is to determine the impact of isolation processes on the emergency care of all patients. Methods: The REC Project builds on the COVID‐19 Emergency Department Quality Improvement (COVED) Project. Outcomes measured include times to critical assessment and management. Results: Clinical tools will be generated to inform emergency care, both during and beyond the COVID‐19 pandemic. Conclusions: The REC Project will support ED clinicians in the emergency care of all patients.